2021
DOI: 10.3389/fped.2021.679279
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Exome Sequencing Identified a Novel Frameshift Mutation of α-Actin 1 in a Chinese Family With Macrothrombocytopenia and Mild Bleeding

Abstract: Inherited macrothrombocytopenia (IMTP) is a rare disorder characterized by a reduced platelet count and abnormally large platelets. The main clinical symptom of IMTP is mild bleeding in some patients. At present, more than 30 genes have been identified in patients with syndromic and non-syndromic IMTP. In this study, a 3-year-old boy and his mother who presented with mild epistaxis and/or gingival bleeding were diagnosed as having IMTP. Wen then selected whole sequencing to explore the genetic lesion of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In this study, the same rare variant mentioned above (rs117672662) was linked to alteration in mean platelet volume and platelet distribution width, while a different, more common variant was associated with mean platelet volume, albeit with a smaller effect size. Finally, a case of ACTN1-linked CMTP involving a frameshift mutation in ACTN1 has recently been reported [90]. This mutation is expected to cause production of a severely truncated protein and decreased levels of intact actinin-1 were reported.…”
Section: Effects Of Actinin-1 Expression Levels On Platelet Productionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, the same rare variant mentioned above (rs117672662) was linked to alteration in mean platelet volume and platelet distribution width, while a different, more common variant was associated with mean platelet volume, albeit with a smaller effect size. Finally, a case of ACTN1-linked CMTP involving a frameshift mutation in ACTN1 has recently been reported [90]. This mutation is expected to cause production of a severely truncated protein and decreased levels of intact actinin-1 were reported.…”
Section: Effects Of Actinin-1 Expression Levels On Platelet Productionmentioning
confidence: 97%
“…Subsequently, these and additional novel mutations were identified in other patient cohorts. A review in 2017 catalogued 20 mutations [4] and more recent studies have brought the total number of different CMTP-causing actinin-1 mutations identified to approximately 40 [86][87][88][89][90]. With one exception (Luo 21; see below), these are all missense mutations that change a single amino acid within the actinin-1 protein, and all appear to be inherited in a dominant fashion.…”
Section: Discovery Of Cmtp-causing Actinin-1 Mutationsmentioning
confidence: 99%